Social And Professional Readiness Of Bachelor's Degree Holders To Work Activities - Shitova, Nina (2018)
The paper presents the results of the empirical study of the social and professional readiness of the bachelor. The main sources were on academic progress and students 'learning experience, diagnostic results of social integration and ability to cope with stress, and also graduates' subjective perception of their educational background for professional engagement. The questionnaire was developed in the course of the process of employment and adaptation in the process of employment in the work of collectives.